A tale of 141 municipalities: the spatial distribution of dengue in Mato Grosso, Brazil - Fernandes, Keli Aparecida Paludo; de Almeida Filho, Ariel Rocha; Alves, Taynná Vacaro Moura; Bernardo, Christine Steiner São; Montibeller, Maria Jara [UNESP]; Mondini, Adriano [UNESP]; de Morais Bronzoni, Roberta Vieira (Oxford University Press (OUP), 2023)
Background: In recent years, the state of Mato Grosso has presented one of the highest dengue incidence rates in Brazil. The meeting of the Amazon, Cerrado and Pantanal biomes results in a large variation of rainfall and temperature across different regions of the state. In addition, Mato Grosso has been undergoing intense urban growth since the 1970s, mainly due to the colonization of the Mid-North and North regions. We analyzed factors involved in dengue incidence in Mato Grosso from 2008 to 2019. Methods: The Moran Global Index was used to assess spatial autocorrelation of dengue incidence using explanatory variables such as temperature, precipitation, deforestation, population density and municipal development index. Areas at risk of dengue were grouped by the Local Moran Indicator. Results: We noticed that areas at risk of dengue expanded from the Mid-North region to the North; the same pattern occurred from the Southeast to the Northeast; the South region remained at low-risk levels. The increase in incidence was influenced by precipitation, deforestation and the municipal development index. Conclusions: The identification of risk areas for dengue in space and time enables public health authorities to focus their control and prevention efforts, reducing infestation and the potential impact of dengue in the human population.
Keywords: arbovirus; spatial analysis; surveillance; vector-borne disease